ECONOMIC ANALYSIS OF LOGISTICS COOPERATION BETWEEN UZBEKISTAN AND CHINA - Xamitova Mavluda Sindarovna; Shokirov Davron Shuxratovich (American Journals Publishing, 2025)
This article provides an economic analysis of the Republic of Uzbekistan's cooperation with the People's Republic of China and the Russian Federation in logistics. The study examines the development of existing transport corridors and logistics infrastructure, their impact on foreign trade turnover, and the significance of this cooperation for the national economy. It also highlights opportunities to increase export potential, strengthen the competitiveness of domestic products, and reduce their costs by improving the logistics system.
Keywords: Logistics, transport corridor, foreign trade, China, Russia, cooperation, infrastructure, economic efficiency.